Leptospira species molecular epidemiology in the genomic era - Caimi, Karina Cynthia; Repetto, Silvia A.; Varni, Vanina Delia; Ruybal, Paula (Elsevier, 2018)
Leptospirosis is a zoonotic disease which global burden is increasing often related to climatic change. Hundreds of whole genome sequences from worldwide isolates of Leptospira spp. are available nowadays, together with online tools that permit to assign MLST sequence types (STs) directly from raw sequence data. In this work we have applied R7L-MLST to near 500 genomes and strains collection globally distributed. All 10 pathogenic species as well as intermediate were typed using this MLST scheme. The correlation observed between STs and serogroups in our previous work, is still satisfied with this higher dataset sustaining the implementation of MLST to assist serological classification as a complementary approach. Bayesian phylogenetic analysis of concatenated sequences from R7-MLST loci allowed us to resolve taxonomic inconsistencies but also showed that events such as recombination, gene conversion or lateral gene transfer played an important role in the evolution of Leptospira genus. Whole genome sequencing allows us to contribute with suitable epidemiologic information useful to apply in the design of control strategies and also in diagnostic methods for this illness.